KONTEKSTUALISASI MAKNA SYAFAAT DALAM AL-QUR’AN - Dahliati Simanjuntak (Journal Khafi : Journal Of Islamic Studies, 2023)
This study seeks to clarify the concept of "Syafa'at" according to the verses of the Koran. Shafa'a consists of the basic words Sin, Fa, and Ain which mean prayer, supplication, intercession, and protection, and is one of the words that has long caused a lot of debate among Islamic scholars. This discussion raises the question of whether intercession exists or not on the Day of Judgment, and who has the right to give and receive it, both its function and its benefits. The topic of Shafaa is interesting to listen to and study in depth. This work tries to capture the interpretation of verses about syafa'a, but what is actually meant by syafa'a itself? In conducting the research, the author used pure literature research based on the verses of the Qur'an relating to the words Syafa'at in the Qur'an by presenting various interpretations of the commentators. the Tafsir book as the primary data source and other books that discuss this matter as secondary data. Meanwhile, the method used in this research is the analytical descriptive method. In other words, we will explain the interpretation of the Shafaa verse comprehensively, separating one meaning from another, and clarifying it so that the following information is obtained: problem. From this study, it is clear that a person must truly believe in the existence of Shafaa, ordinary prophets, angels, people who do good deeds, these Shafaa were given by Allah SWT through the mediation of Rasulullah SAW. Infidels who reject the prophethood of the Prophet Muhammad SAW, and polytheists or other infidels. Meanwhile, the method used is the Tahlili method. The purpose of this research is to examine how the concept of intercession explains the meaning of intercession, who receives intercession, what intercession can do, and the regrets of unbelievers due to the absence of intercession. Next, you must know the views of the ulama regarding the importance of intercession. From the research results, the definition of intercession is prayer, and those who receive intercession are people who have done good and praiseworthy deeds while living in that world, and that is the ticket to obtain intercession. However, if someone commits evil and destructive actions during his lifetime, then he will not receive intercession. It is also important for Muslims who read Kalima Toibah at the time of death so that Allah will intercede when someone ends their life in the world, which is in the Book of Revelation, and intercession in the afterlife which will occur later in the Book of Revelation. Whoever does it is essentially God who gives special privileges.